Stunning methods and slaughter of rabbits for human consumption. (9th January 2020) - ,; Saxmose Nielsen, Søren; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Depner, Klaus; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortázar Schmidt, Christian; Michel, Virginie; Miranda Chueca, Miguel Ángel; et al.
Abstract: This opinion on the killing of rabbits for human consumption ('slaughtering') responds to two mandates: one from the European Parliament (EP) and the other from the European Commission. The opinion describes stunning methods for rabbits known to the experts in the EFSA working group, which can be used in commercial practice, and which are sufficiently described in scientific and technical literature for the development of an opinion. These are electrical stunning, mechanical stunning with a penetrative and non‐penetrative captive bolt and gas stunning. The latter method is not allowed in the EU anymore following Council Regulation (EC) No 1099/2009, but may still be practiced elsewhere in the world. Related hazards and welfare consequences are also evaluated. To monitor stunning effectiveness as requested by the EP mandate, the opinion suggests the use of indicators for the state of consciousness, selected on the basis of their sensitivity, specificity and ease of use. Similarly, it suggests indicators to confirm animals are dead before dressing. For the European Commission mandate, slaughter processes were assessed from the arrival of rabbits in containers until their death, and grouped in three main phases: pre‐stunning (including arrival, unloading of containers from the truck, lairage, handling/removing of rabbits from containers), stunning (including restraint) and bleeding (including bleeding following stunning and bleeding during slaughter without stunning). Ten welfare consequences resulting from the hazards that rabbits can be exposed to during slaughter are identified: consciousness, animal not dead, thermal stress (heat or cold stress), prolonged thirst, prolonged hunger, restriction of movements, pain, fear, distress and respiratory distress. Welfare consequences and relevant animal‐based measures (indicators) are described. Outcome tables linking hazards, welfare consequences, indicators, origins, preventive and corrective measures are developed for each process. Mitigation measures to minimise welfare consequences are also proposed.